Short Communication: Diversity, distribution and potential uses of Ficus spp. in Sumatra, Indonesia - SILVIA INDRA DEWI; SYAMSUARDI SYAMSUARDI; NURAINAS NURAINAS (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Dewi SI, Syamsuardi, Nurainas. 2023. Short Communication: Diversity, distribution and potential uses of Ficus spp. in Sumatra, Indonesia. Biodiversitas 24: 3431-3438. The Andalas Herbarium is the largest herbarium in Sumatra, with specimens totaling 34,850 sheets and 2011 species of vascular plants from 126 familiesand 491 genera. It serves as a valuable resource for the study of biodiversity, particularly on the island of Sumatra. The purpose of this study was to examine the diversity, distribution, and potential uses of Ficus spp. in Sumatra based on Andalas Herbarium (ANDA) specimens. A total of 2300 herbarium sheets were examined, resulted in 53 species of Ficus spp. collected at Andalas Herbarium. The Ficus at Andalas Herbarium consists of six subgenera, namely Ficus, Pharmacosycea, Sycidium, Sycomorus, Synoecia, and Urostigma. The subgenus with the highest number of species is Urostigma while the lowest is Pharmacosycea.Our examination found the new occurrence of F. rubrocuspidata in West Sumatra. The herbarium specimens were mostly collected from Padang city and least collected from Kampar District. In general, all species of Ficus were found in lowlands and some species were found in highlands. Among the Ficus species recorded at Andalas Herbarium, 63% have the potential uses as medicine, ornamental plants, or consumed as young shoots and fruit.